WHAT IS NEW IN MANAGEMENT OF CHILDREN AND ADOLESCENTS WITH COELIAC DISEASE - Katja Podbregar; Tina Kamhi Trop (The Society for Children with Metabolic Disorders, 2024)
In this paper, we present the new guidelines for diagnosing coeliac disease and the new position statement on the management and follow-up of patients with coeliac disease. Following up on children and adolescents with coeliac disease is necessary for the education and support of children and their families and, at the same time, for identifying children with insufficient improvement following a gluten-free diet. Visits to the outpatient clinic should be scheduled at shorter intervals until the normalization of serology. However, they can be less frequent later on. At each visit, adherence to the gluten-free diet is assessed using questionnaires, symptoms and signs, and serology. So far, there is no suitable scientific method that could be used to evaluate adherence to the diet. It is also essential to look for possible disease complications at follow-up visits. Coeliac disease can have a negative impact on the emotions, social relationships and daily life of children and adolescents, so it is necessary to assess the health-related quality of life and empower children and their families to cope with possible problems. The transition to adult health care should be initiated, planned and organized during adolescence.